Pathologists' professional lifestyle: Excellence in practice, ethics, education, health promotion, and personal life - Navid Omidifar; Aref Hafezi Bafti; Mansoureh Shokripour; Mitra Amini; Irma Elisa Erana-Rojas; Mohammadali Moghimizadeh (Wolters Kluwer Medknow Publications, 2022)
For a successful treatment process, the medical team members must be in good physical and mental condition. Pathologists are one of the main modern medicine members that should be consulted in all stages of the treatment procedure. Sixty-six percent of clinical decisions are made based on in vitro diagnosis. Burnout is defined as chronic uncontrolled occupational stress. Burnout has a massive impact on patient safety, quality of treatment, and reduced patient satisfaction. Physician satisfaction with his job affects patient satisfaction and the quality of medical services provided. The most influential factors on quality of life were exercise and physical activity, having leisure time, and not smoking. In different aspects of lifestyle, physicians have scored lower on their physical activity index. One of the most critical pillars of human life is their religiosity. The presence of religious beliefs among physicians is strong. Workload and increased responsibilities are the most effective factors on pathologists' stress. Pathology creates a bridge between basic sciences and clinical sciences. Therefore, promoting pathology education leads to training better physicians. The purpose of compiling this Narrative review is to clarify the issues raised in various aspects of pathologists' lives and provide solutions to improve each of them. There are several solutions to the problems raised in this article: Increasing salaries, improving working conditions, creating a better view of pathologists by avoiding isolation and being more active and visible, and paying attention to medical education. We recommend that researchers review issues in other medical specialties to provide accurate and concise information to physicians and policymakers.